Pioneers of Medical Profession in Pakistan: Contributions of Armed Forces Doctors - Akhtar, Mahmud Ahmed (Pakistan Armed Forces Medical Journal, 2025)
It is nice to remember the pioneers of the medical profession in Pakistan. In the Civil setup, the Armed Forces personnel are generally not well known, and their contributions are often overlooked in published articles. In this article, the contributions of the Armed Forces doctors as pioneers and their role in developing the medical profession in the early period of Pakistan are described. At independence, the Pakistan Armed Forces inherited well-developed psychiatric units at major Military Hospitals with both indoor and outdoor facilities. Military Hospital Rawalpindi had a major psychiatric unit, which also trained postgraduates. Maj M. Shoaib (later Maj Gen) was the Head of the unit. He was trained in psychiatry before the partition and was the first to acquire D.P.M. (Lond) from Pakistan (at that time, it was the major qualification in psychiatry). CMH Lahore had a well-known psychiatrist, Maj Thaker Das. Later, Major General Ishrat Hussain and Brigadier Fazle-Haq made contributions. In the civil institutions, psychiatric units emerged decades later.